2007
DOI: 10.1021/jf0636418
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Characterization of the Aroma of Five Premium Red Wines. Insights into the Role of Odor Families and the Concept of Fruitiness of Wines

Abstract: The aroma profile of five premium red wines has been studied by sensory descriptive analysis, quantitative gas chromatography-olfactometry (GC-O), and chemical quantitative analysis. The most relevant findings have been confirmed by sensory analysis. Forty-five odorants, including the most intense, were identified. At least 37 odorants can be found at concentrations above their odor threshold. A satisfactory agreement between GC-O and quantitative data was obtained in most cases. Isobutyl-2-methoxypyrazine, (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
374
10
13

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 516 publications
(425 citation statements)
references
References 36 publications
28
374
10
13
Order By: Relevance
“…4, the predicted flavour contribution of the total MPs (based on Allen & Lacey, 1998) to the analysed South African wines is given as a function of percentage of the total number of samples. It should be noted that, due to synergistic interactions between various aroma compounds, sensory properties and consumer preference of Sauvignon blanc wines are difficult to predict with great precision (Escudero et al, 2007;King et al, 2011), and the flavour descriptions used in the current context refer to the probable effect that these compounds may have on the aroma of the wines. The predicted flavour descriptions range from below recognition through to overpowering and out of balance, with 18% of the samples falling in the narrow concentration window where their contribution may be regarded as positively favourable to the vegetative Sauvignon blanc wine aroma.…”
Section: Investigation Of the Occurrence Of Mmp And Emp In South Afrimentioning
confidence: 99%
“…4, the predicted flavour contribution of the total MPs (based on Allen & Lacey, 1998) to the analysed South African wines is given as a function of percentage of the total number of samples. It should be noted that, due to synergistic interactions between various aroma compounds, sensory properties and consumer preference of Sauvignon blanc wines are difficult to predict with great precision (Escudero et al, 2007;King et al, 2011), and the flavour descriptions used in the current context refer to the probable effect that these compounds may have on the aroma of the wines. The predicted flavour descriptions range from below recognition through to overpowering and out of balance, with 18% of the samples falling in the narrow concentration window where their contribution may be regarded as positively favourable to the vegetative Sauvignon blanc wine aroma.…”
Section: Investigation Of the Occurrence Of Mmp And Emp In South Afrimentioning
confidence: 99%
“…This can be attributed to the fact that GC-O analysis essentially evaluates the aroma of the compounds individually and separate from the sample matrix. GC-O does not take into account the interaction effects that occur when aroma compound interact with the nonvolatile matrix (Pineau et al 2007, Robinson et al 2009, Sáenz-Navajas et al 2010, 2012 and with other volatile compounds (Atanasova et al 2005b, Escudero et al 2007, Pineau et al 2009). As discussed later, these interactions may result in variations in the sensory character of the mixture due to enhancement and suppression effects.…”
Section: Gc-olfactometrymentioning
confidence: 99%
“…For example, using descriptive analysis, it has been shown that fruity aromas in wines can significantly mask vegetal characters in the wines (Hein et al 2009). Similarly, at low concentrations, β-damascenone has the ability to mask the herbaceous aroma associated with 3-isobutyl-2-methoxypyrazine (Pineau et al 2007) while enhancing the berry fruit aromas in red wines (Escudero et al 2007, Pineau et al 2007). As noted in the above section, the aromas of wine blends exhibited suppressive and amplifying effects when the intensity of specific aroma attributes of the blends was compared to the original aroma of the monovarietal wines (Hopfer et al 2012a).…”
Section: Sensory Evaluation Of Winementioning
confidence: 99%
See 1 more Smart Citation
“…These compounds were present in low concentration in all vintages. -damascenone is normally considered a positive contributor to wine aroma (Escudero et al, 2007) and its odor threshold (0.05 μg/l) (Guth, 1997) was exceeded in 2007, 2009 and 2010 vintages. Floral and exotic fruit notes are attributed to -damascenone, and due to its low odour threshold it can have a great sensorial impact on wines (Guth, 1997).…”
Section: Varietal Aroma Compoundsmentioning
confidence: 99%